Parents’ experiences and perceptions of the acceptability of a whole-hospital, pro-active electronic pediatric early warning system (the DETECT study): A qualitative interview study - Saron, Holly; Carter, Bernie; Siner, Sarah; Preston, Jennifer; Peak, Matthew; Mehta, Fulya; Lane, Steven; Lambert, Caroline; Jones, Dawn; Hughes, Hannah; Harris, Jane; Evans, Leah; et al. (Frontiers in Pediatrics, 2022)
Abstract Background Failure to recognise and respond to clinical deterioration in a timely and effective manner is an urgent safety concern, driving the need for early identification systems to be embedded in the care of children in hospital. Paediatric early warning systems (PEWS) or PEW scores alert health professionals (HPs) to signs of deterioration, trigger a review and escalate care as needed. PEW scoring allows HPs to record a child’s vital signs and other key data including parent concern. Aim This study aimed to explore the experiences and perceptions parents about the acceptability of a newly implemented electronic surveillance system (the DETECT surveillance system), and factors that influenced acceptability and their awareness around signs of clinical deterioration and raising concern. Method Descriptive, qualitative semi-structured telephone interviews were undertaken with parents of children who had experienced a critical deterioration event (CDE) (n=19) and parents of those who had not experienced a CDE (non-CDE parents) (n=17). Data were collected between February 2020 and February 2021. Results Qualitative data were analysed using generic thematic analysis. Analysis revealed an overarching theme of trust as a key factor that underpinned all aspects of children’s vital signs being recorded and monitored. The main themes reflect three domains of parents’ trust: trust in themselves, trust in the HPs, and trust in the technology. Conclusion Parents’ experiences and perceptions of the acceptability of a whole-hospital, pro-active electronic paediatric early warning system (The DETECT system) were positive; they found it acceptable and welcomed the use of new technology to support the care of their child.